Developed Dijkstra shortest path search algorithm and simulation - Yin Chao; Wang Hongxia (2010 International Conference On Computer Design and Applications, 2010)
This paper presents an improved Dijkstra shortest path search algorithm. The algorithm considers the different types of weights, set the priority target search region, reduce the large number of meaningless operations, in order to improve search efficiency. We do some relevant testing based on the shortest distance and shortest time through simulation. The simulation show that the improved Dijkstra shortest path search algorithm can reduce the computation time.